The Mediating Effect of Organizational Learning on the Relationship between the Cost Leadership Strategy and Business Performance: A Study on Travel Agencies - Ramazan Kaya; Mehmet Akif Öncü; Muammer Mesci (Journal of Economy Culture and Society)
The aim of this research is to investigate the mediating role of organizational learning in the relationship between cost leadership strategy and business performance. The universe of the research is composed of middle and senior managers of The International Air Transport Association (IATA) member travel agencies operating throughout Turkey. Quantitative research method was conducted and the data were obtained by face-to-face and email survey techniques. The data of the 351 questionnaires evaluated were analyzed using the Structuralthe Structural Equation Modeling (SEM) AMOS package program. The results of the study indicate a positive relationship between cost leadership strategy and business performance. In addition, organizational learning plays a mediator role between cost leadership strategy and business performance. These results once again reveal the importance of cost leadership strategy and organizational learning in achieving desired performance goals in travel agencies. The population of this study is limited to IATA member travel agencies. Future research should review this limitation to improve rigorousness and generalisability. The population of this study was restricted to travel agencies. Comparative studies involving hotel and transportation establishments, and thereby changing the universe, will contribute to the relevant literature and provide more effective results.